DEFORMATION OF HUMAN NATURE IN ERICH FROMM'S SOCIAL-EXISTENTIAL CONCEPT (Scientific journal of the Fergana State University, 2025)
Erich Fromm's existential philosophy analyzes human nature, the factors that shape it, the desire for dominance or submission in people, the content and social significance of love and hatred for life.